10x-6=4+5x

Simple and best practice solution for 10x-6=4+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-6=4+5x equation:


Simplifying
10x + -6 = 4 + 5x

Reorder the terms:
-6 + 10x = 4 + 5x

Solving
-6 + 10x = 4 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-6 + 10x + -5x = 4 + 5x + -5x

Combine like terms: 10x + -5x = 5x
-6 + 5x = 4 + 5x + -5x

Combine like terms: 5x + -5x = 0
-6 + 5x = 4 + 0
-6 + 5x = 4

Add '6' to each side of the equation.
-6 + 6 + 5x = 4 + 6

Combine like terms: -6 + 6 = 0
0 + 5x = 4 + 6
5x = 4 + 6

Combine like terms: 4 + 6 = 10
5x = 10

Divide each side by '5'.
x = 2

Simplifying
x = 2

See similar equations:

| 24-x^2-12x=0 | | f(x)=10x^4+7x^3-27x^2+2x+8 | | x^2+3x-1=17 | | (4x+11)+(3x+1)=180 | | (x-2)(x-2)(1)=169 | | 21x=3/4 | | (x+10)+(3x+18)=180 | | -20(3x-68)=-80(9x-38) | | (2x-5)+(4x-13)=90 | | 3x+7z=2-2y | | 4a^2=25a+21 | | 7(a-6)+13=3(a-7) | | 4(x+5)-3=23-2x-6+6x | | 7a-7a=15 | | 7(-6)+3y=12 | | 240=2x^2+2x | | 33%+14%= | | 10(x+5)=3(4x+3) | | .25x-.05=.2x+.15 | | .1(x+74)=2(2-x) | | 2x^3+13s^2+20s+20=0 | | 4xy+7xy+12xy+14xy= | | 2a-7=3(a+1)+9a+1 | | 2x-1=3.2 | | 2h^2-32=0 | | -52-18=x | | x+sqrt(5x+19)=-1 | | -20+(-17)=x | | 5ln(3y+45)=5 | | 11n-n^2=0 | | (x*0.8)+(x*0.7)+(x*0.95)=17000 | | x^4-19xy^6+41x^3y^8-2x^4y^6= |

Equations solver categories